Teaching Workload in 21st Century Higher Education Learning Setting - Hamimah, Ujir; Shanti Faridah, Salleh; Hashimatul Fatma, Hashim; Ade Syaheda Wani, Marzuki (2019)
A standard equation on teaching workload calculation in the previous setting only includes the contact hours with students through lecture, tutorial, laboratory and face to face consultation. This paper discusses teaching workload factors according to the current higher education setting. Devising a teaching workload equation that includes all teaching and learning 21 51 strategies in century higher education learning setting is needed. Teaching workload also affects quality teaching as the higher workload means a lower quality teaching.